PENGARUH PAD, DANA PERIMBANGAN, LPDS, DAN PDRB PADA BELANJA DAERAH SERTA DETEKSI ILUSI FISKAL - Pratami, A. A. Putu Nandya Indah; Dwirandra, A. A. N. B. (E-Jurnal Akuntansi, 2017)
The purpose of this study was to obtain empirical evidence of the effect of local revenue (the proxy for local taxes and HCT), balancing fund (which is proxied by DAU, DAK and DBH), LPDS and PDRB at shopping areas and the presence or absence of a fiscal illusion on financing regional expenditure. The population in this study were 8 counties and 1 city in Bali in 2010-2014. The number of samples that 45 was obtained using the technique of saturated samples. Analysis of the data used in this research is multiple linear regression analysis. This study found that local taxes and DAU positive and significant impact on shopping areas, LPDS and PDRB has positive and not significant to shopping areas, while the HCT, DAK and DBH not significant and negative to shopping areas. In addition, the study also found that there is no fiscal illusion.
Keywords: Local Revenue, Balancing Fund, Local Expenditure, Fiscal Illusion